Incidencia de las actividades físico deportivas en el índice de masa corporal de las personas sedentarias del Sector Playas de Vinces 2022 - Morales Candelario, Cindy Isabela (2022)
The present investigation had the purpose of analyzing the incidence of physical sports activities on the body mass index of sedentary people in the Playas de Vinces 2022 sector. A non-experimental research design of descriptive cross-section was used. Likewise, anthropometric measurements were applied to calculate the body mass index and a survey to measure the degree of satisfaction towards physical sports activities to a selected non-probabilistic sample of 20 sedentary people (8 adolescents and 12 adults), for subsequent analysis. in relation to physical sports activities and the body mass index of sedentary people in the Playas de Vinces sector through bibliographic review and field research respectively. Among the results obtained, physical sports activities were established as an incident means towards the body mass index of sedentary people in the Vinces beach sector, through the proposal of a plan of physical sports activities.